Spectrophotometric Determination of Some Phenolic Compounds Using N,N- diethyl -p-phenylenediamine (DE - PPD) and Benzoyl peroxide - Elham S. Salih; M. M. Al- sharook; Saladdin M. AL-Talib (College of Education for Pure Sciences, 2013)
ABSTRACT A rapid and sensitive spectrophotometric method has been developed for the determination of some phenolic compounds (phenol, o-aminophenol and α-naphthol) and was applied for determination of amoxicillin drug. The method is based on oxidative coupling reaction of these compounds with N,N-diethyl-p-phenylenediamine in the presence of benzoyl peroxide as oxidizing agent. The formed blue indophenol dyes have maximum absorptions at 627, 612.5, 611.5 and 628.5 nm. for phenol, o-aminophenol, α-naphthol and amoxicillin respectively. The molar absorptivities are 1.72× 104, 1.92× 104, 1.65 × 104. l. mol1-. cm-1 for concentrations obeyed Beer,s law in the ranges 0.2 -4.0, 0.5 -11.0, 0.6 - 16.0 and 0.8 - 25.0 µg ml-1 for the above compounds respectively. The average recovery % was ranged between 98.99% 100.45 with relative standard deviation ≤ 1.04 for all the studied compounds. The method is applied